FILLERS USED BY MALE AND FEMALE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM IN ARGUMENTATIVE TALKS - Lerry Navratilova (Linguists : Journal Of Linguistics and Language Teaching, 2015)
This research aimed at find outtypes and function of fillers used by male and female students of the English Education Study Program in argumentative talks. This research was descriptive research. The subjects consisted of two students groups: male and female students each consisting of four students. The data were fillers used by the students from the transcript of 2 10- minute argumentative talks. The data were analyzed and classified based on the theory proposed by Rose (1994). Then, functions of fillers based on theory by Strenstrom in Kurwanto (2011). The results show that  the male and female students produced unlexicalized fillers as the most frequently used, followed by lexicalized fillers. Both of male and female students  produced fillers in order to fill pause, to hesitate, to hold conversation turn, to emphatize, to mitigate, to intterupt, and to edit their speech error. All those function of fillers proposed by Strenstrom were used by male and female students in their talks . In addition, Filling pause was the most frequently function used by male and female students, followed by fillers as a mark of hesitation. Thus,  there were similiarities both in types and functions used by male and female students. However, the researcher found female students produced more fillers than men did. This maybe due to women tend to speak less certainty compared to male